The future is history : how totalitarianism reclaimed Russia - Gessen, Masha (Riverhead Books, 2017)
Award-winning journalist Masha Gessen's understanding of the events and forces that have wracked Russia in recent times is unparalleled. In The Future Is History, Gessen follows the lives of four people born at what promised to be the dawn of democracy. Each of them came of age with unprecedented expectations, some as the children and grandchildren of the very architects of the new Russia, each with newfound aspirations of their own--as entrepreneurs, activists, thinkers, and writers, sexual and social beings. Gessen charts their paths against the machinations of the regime that would crush them all, and against the war it waged on understanding itself, which ensured the unobstructed reemergence of the old Soviet order in the form of today's terrifying and seemingly unstoppable mafia state. Powerful and urgent, The Future Is History is a cautionary tale for our time and for all time.